Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/srep19541
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of a rapid and minimally instrumented sputum sample preparation method for molecular diagnosis of tuberculosis

Abstract: Nucleic acid amplification testing (NAAT) enables rapid and sensitive diagnosis of tuberculosis (TB), which facilitates treatment and mitigates transmission. Nucleic acid extraction from sputum constitutes the greatest technical challenge in TB NAAT for near-patient settings. This report presents preliminary data for a semi-automated sample processing method, wherein sputum is disinfected and liquefied, followed by PureLyse® mechanical lysis and solid-phase nucleic acid extraction in a miniaturized, battery-op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Interestingly, GSCN by itself showed very efficient results in terms of sputum liquefaction, even when combined with the other chemicals. It has been previously shown that concentrated GSCN can be used in sample preparation for the extraction of DNA and protein from a variety of samples [25], and even using an electricity-free protocol [26] or small battery-operated instruments [27]. More importantly, M. tuberculosis was shown to become non-viable after exposure to commercial lysis buffers, which contain concentrated guanidine [8].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, GSCN by itself showed very efficient results in terms of sputum liquefaction, even when combined with the other chemicals. It has been previously shown that concentrated GSCN can be used in sample preparation for the extraction of DNA and protein from a variety of samples [25], and even using an electricity-free protocol [26] or small battery-operated instruments [27]. More importantly, M. tuberculosis was shown to become non-viable after exposure to commercial lysis buffers, which contain concentrated guanidine [8].…”
Section: Discussionmentioning
confidence: 99%
“…The sputum specimen pre-treatment procedures and protocols used to diagnose pathogens such as tuberculosis and pneumonia are complex and very labor intensive. The protocol involves liquefaction, homogenization, dissolution, and inactivation 11 , 12 . The pre-treatment methods for infectious sputum specimens currently used in most laboratories require not only daily preparation of reagents but also the process of opening and closing the lid for adding reagents, vortex mixing, and sedimentation using a centrifuge—all of which are done by hand 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…It can identify drug resistance and provides early results. The GeneXpert MTB is the most widely used TB nucleic acid amplification testing system, and is recommended for use in areas where TB and multidrug‐resistant TB are prevalent …”
Section: Discussionmentioning
confidence: 99%